Expression of resistance to Phytophthora infestans in climatic chamber-, screenhouse- and field-grown wild potato species in a detached leaflet assay - Zoteyeva, Nadezhda (Plant Breeding and Seed Science, 2004)
A study on the expression of resistance to Phytophthora infestans of wild potato plants grown in a climatic chamber, in a screenhouse and in the field was performed in two experiments. In the first experiment 12 populations of Solanum acaule were tested. Detached leaves from field-grown plants appeared to be less resistant than detached leaves from chamber-grown plants. In the second experiment resistance responses to inoculation with P. infestans of 24 Solanum species, grown in the field and in the screenhouse were compared. In 18 populations belonging to 11 species the predominance of resistant plants was found either when plants were grown in the field or when plants were grown in the screenhouse. Within 12 tested populations no difference in resistance was observed because of high susceptibility of plants, irrespective of grown conditions. Two populations showed the same level of resistance under both grown conditions.